Brewer’s Spent Dry Yeast Modulates Immunity in Gilthead Sea Bream (Sparus aurata) - Konstantinidis, Ioannis; Firmino, Joana P.; Ruiz, Alberto; Iñarra, Bruno; San Martin, David; Estévez, Alicia; Fernandes, Jorge M. O.; Gisbert, Enric (Frontiers in Marine Science, 2022)
In this study, we evaluated the replacement of dietary protein sources like fishmeal (FM) and plant proteins (PP) by Brewer’s spent dry yeast (SDY) on the transcriptomic response (RNA-seq, NextSeq500 platform Illumina) in the liver, anterior-mid intestine, and head kidney in juveniles of gilthead sea bream (Sparus aurata). The inclusion of SDY at 30% in the experimental diet (40% crude protein, 16% crude lipid) resulted in a reduction in FM (10%) and PP (31.4%) contents. Using RNAseq, a total of 19.4 million raw reads per library were obtained, from whose 99.8% of the sequenced data were retained. The alignment efficiency of uniquely mapped reads was 90.3%, 89.5% and 89.8% for head kidney, liver, and anterior-mid intestine, respectively. In total, 218 differentially expressed genes (DEGs) were identified among all tissues, out of which, 141 were up- and 77 down-regulated. The enrichment analysis of DEGs revealed that SDY had a modulatory effect on several processes related to host’s immunity, oxygen’s carrier capacity, steroidogenesis, metabolism, and digestion. It is of special relevance the immunomodulatory effects of the tested ingredient as data from RNA-seq showed from the three target tissues analysed. These results indicated that this ingredient in addition to be considered as a sustainable raw material for replacing conventional protein sources in aquafeeds, it may also be considered as a functional ingredient due to its content in β-glucans. The overall results of this study coupled by previous nutritional studies on this ingredient indicated the suitability of brewery’s by-products like SDY in aquafeeds for carnivorous species like gilthead seabream, as well as supporting a circular bioeconomy model that reuses, recovers and recycles resources instead of producing wastes.